SCIENTIFIC AND METHODOLOGICAL APPROACH TO DIAGNOSTICS OF THE LEVEL OF THE CITY ECOLOGICAL SAFETY SYSTEM - Тарасевич, Олена; Жилінська, Людмила (SWorldJournal, 2022)
The paper identifies that the implementation of state environmental policy requires the adoption of new methods for diagnosing the level of environmental safety of cities to implement new projects and programs for environmental development of regions. Th